Efektifitas Penerapan Metode Iqro’ terhadap Kefasihan Santri Membaca Al-Qur’an di PPA. Lubangsa Putri - Abdul Halim (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2021)
Islamic boarding schools as centers of Islamic religious learning are the most appropriate places to learn to read and study the Qur'an as the main source and reference for Muslims in behavior. however, not all students who study religion in Islamic boarding schools have the ability and fluency in reading the Qur'an. This research was conducted at the Annuqayah Lubangsa Putri Islamic Boarding School which intends to measure the level of fluency in reading the Qur'an by using the iqro’ method for students who are at the junior and senior high school formal education levels. This study uses a qualitative method to measure the effectiveness of the application of the iqro’ method at the Annuqayah Lubangsa Putri Islamic Boarding School. This research uses observation, interview, documentation, and triangulation techniques, while the analysis technique used is data reduction, data presentation, and conclusion drawing. This study shows that the application of the iqro’ method is considered effective in increasing the fluency of reading the Qur'an of students at the Annuqayah Lubangsa Putri Islamic Boarding School. This is because, the application of the iqro’ method is very appropriate especially for students who experience age delays in learning to read the Qur'an. The application of the iqro’ method cannot be separated from the role of the Islamic Guidance and Development (BPK) administrator and the supervisor of the Qur'an reading in improving the fluency of reading the Qur'an of students.